Analytical considerations for (un)‐targeted metabolomic studies with special focus on forensic applications. Issue 5 (28th November 2018) - Boxler, Martina I.; Schneider, Tom D.; Kraemer, Thomas; Steuer, Andrea E.
Abstract: Over the past few years, the interest in metabolomics has increased in various fields including forensic toxicology. Forensic analysis typically requires a high degree of accuracy, which is often a problem in metabolomics applications. We aimed for a systematic evaluation of different analytical considerations of a metabolomics workflow allowing a targeted approach within an untargeted setup. Samples with 69 metabolites from different chemical classes were qualitatively and quantitatively analyzed on a high resolution quadrupole time of flight mass spectrometer coupled to liquid chromatography (UHPLC–QTOF). Three issues were addressed: (a) Two different approaches on "blind matrix" a simulated body fluid (SBF) and plasma‐filtrate, were tested for calibration samples; (b) comparison of two different HPLC columns, reverse‐phase (RP) and hydrophilic interaction chromatography (HILIC); and (c) comparison of three different acquisition modes (TOF–MS, information dependent data acquisition (IDA), and sequential window acquisition of all theoretical fragment‐ion spectra (SWATH). Samples were measured repeatedly for method comparison based on sensitivity, accuracy, precision, and detection robustness. The blind matrices showed similar accuracy for most analytes, while SBF provided an easier preparation with satisfying results. To cover a wide part of the human metabolome, a combination of RP and HILIC showed the best results. The different scan modes performed equally regarding metabolite quantification while TOF–MS was more sensitive but lacked MS/MS spectra generation. IDA and SWATH files were aligned to various databases where IDA showed good MS/MS spectra matches. SWATH seemed to be beneficial in detection rate but was incompatible with many important software tools in metabolomics. Abstract : Different analytical strategies for a metabolomics workflow allowing targeted acquisition within an untargeted workflow were evaluated. Selected metabolites from different chemical classes were analyzed on a high resolution quadrupole‐time‐of‐flight mass spectrometer in a qualitative and quantitative manner. Three different scan modes (TOF MS, IDA, and SWATH) were compared in terms of sensitivity, accuracy, precision, and robustness. In addition, two different HPLC columns (RP and HILIC) as well as two different approaches on providing a "blind matrix" were evaluated.